Effects of low-frequency ultrasound on microcirculation in venous leg ulcers - Uwe Wollina; Birgit Heinig; Gunther Naumann; Armin Scheibe; Wolf-Dieter Schmidt; Reimund Neugebauer (Wolters Kluwer Medknow Publications, 2011)
Background: Therapeutic low-frequency ultrasound (US) has been used for many years to improve wound healing in chronic wounds like venous leg ulcers. No human data are available for the possible effects of single US applications on microcirculation and their frequency-dependency. Aims: To investigated the role of therapeutic low-frequency US on microcirculation of venous leg ulcers in vivo. Patients and Methods: This is a pilot study on an inpatient basis. We use a newly developed low-frequency continuous-wave US-equipment composed of a US transducer based on piezo-fiber composites that allow the change of frequency. In this study, we apply US of 34 kHz, 53.5 kHz, and 75 kHz respectively. Twelve patients with chronic venous leg ulcers are analyzed. As an adjunct to good ulcer care, therapeutic US is applied, non-contacting, once a day, in a subaqual position for 10 minutes. Microcirculation is assessed in the ulcers adjacent to skin before US-therapy, immediately after the treatment and 30 minutes later. We use a micro-light guide spectrophotometer (O2C, LEA Medizintechnik GmbH, Gieίen, Germany) for calculation of blood flow velocity, hemoglobin oxygen saturation (SCO 2 ) and relative hemoglobin concentration (rHb) in 2 and 8 mm depth. Contact-free remission spectroscopy (SkinREM3, Color Control Chemnitz GmbH, Chemnitz, Germany) allows contact free measurements in the VIS-NIR range of the spectrum (400 ± 1600 nm). Results: It is seen that therapeutic US is well tolerated. One patient dropped out from a treatment series since he developed erysipelas responding to standard antibiotic. Effects were seen at 34 kHz only. The SO 2 values increased after single US application. The values for rHb were higher in the superficial layer of the wound bed (depth 2 mm) compared to deeper parts (8 mm depth). US treatment did not result in significant changes of rHb and blood cell velocity. The data obtained by remission spectroscopy disclose an increase of oxygenized hemoglobin. Conclusions: The major findings are that continuous-wave low-frequency US of 34 kHz, but not, 53.5 kHz or 75 kHz, has a temporary stimulatory effect on microcirculation mainly due to an improved oxygenation. Further studies with treatment series are necessary.